Arabic Teacher Professionalism in the Digital Era: Ethical Reflections and Philosophical - Hilmy, M. Insan; Fahraini, Sovia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The digital era brings significant transformation in education, demanding that Arabic language teachers adapt. This article aims to analyze the ethical and philosophical challenges that Arabic teachers face in practicing their professionalism in the digital era and redefine the concept of teacher professionalism that is not only technically skilled but also has a strong ethical-philosophical awareness. The researcher employed a qualitative literature study method. The findings identified two primary challenges: firstly, ethical issues such as concerns over student data privacy, algorithmic bias, and the prevalence of technology that conflicts with Islamic values. Secondly, there are philosophical challenges related to epistemology, ontology, and axiology of Arabic within the digital realm. In conclusion, the professionalism of Arabic language teachers in the digital era must be redefined based on three pillars: digital competence, ethics as a "moral compass," and philosophy as a "reflective thinker" to ensure the wise integration of technology without compromising the values and authenticity of Arabic language learning. It is recommended that Arabic language teachers integrate technology critically, guided by ethical principles and philosophical reflection, to preserve authenticity while enhancing digital competence.